2018
DOI: 10.1108/bij-10-2017-0286
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking higher education programs through alignment analysis based on the revised Bloom’s taxonomy

Abstract: Purpose The purpose of this paper is to propose a scalable quantitative approach to evaluate alignment within and between courses and programs in higher education for benchmarking purpose. Design/methodology/approach The revised Bloom’s taxonomy, which combines a cognitive process dimension and a knowledge dimension, is used as a basis for categorizing national standards, program and course learning outcomes (CLOs) and assessment methods. Alignments between programs and national standards, programs and cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Yet student engagement is fundamentally different from and extends beyond the concept of “academic task accomplishment” (Bergmann and Sams, 2014). Fundamentally, student engagement is defined as a psychological investment and cognitive involvement in understanding, learning, and mastering knowledge, skills and crafts (Zepke and Leach, 2010; Lau et al , 2018). It is more than just completing the assigned tasks or qualifying for commonly accepted measures of success (e.g., grades).…”
Section: Student Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet student engagement is fundamentally different from and extends beyond the concept of “academic task accomplishment” (Bergmann and Sams, 2014). Fundamentally, student engagement is defined as a psychological investment and cognitive involvement in understanding, learning, and mastering knowledge, skills and crafts (Zepke and Leach, 2010; Lau et al , 2018). It is more than just completing the assigned tasks or qualifying for commonly accepted measures of success (e.g., grades).…”
Section: Student Engagementmentioning
confidence: 99%
“…Student engagement is considered a robust measure of student learning (Bergmann and Sams, 2014). Students learn more and master relevant skills when they are engaged in the learning process and acquire feedback on their academic activities such as writing, analyzing and problem-solving (Kuh, 2003; Lau et al , 2018). Engaged students develop exploration and learning habits that strengthen their capacity for personal and professional development (Shulman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the checklists and the collation of the year level team information clearly demonstrated that integration of learning across the programs took place when learning outcomes and content were clearly aligned. The alignment of learning outcomes, curriculum and assessment are necessary to guide instruction and student teacher learning (Lau et al, 2018). This study noted that it was particularly evident when learning outcomes were strongly linked to professional workplace experience.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, various methods of teaching and learning were introduced in order to achieve the objective of teaching and learning. Course Learning Outcome (CLO) is the benchmark of course output [2] that describe what students will know and be able to do upon successful complete a program or course.…”
Section: Introductionmentioning
confidence: 99%